Arsenic in drinking water, hair, and prevalence of arsenicosis in Perak, Malaysia - Ramly, Nurfatehar; Ahmad Mahir, Husna Maizura; Wan Azmi, Wan Nurul Farah; Hashim, Zailina; Hashim, Jamal Hisham; Shaharudin, Rafiza (Frontiers in Public Health, 2023)
Arsenic is a carcinogen element that occurs naturally in our environment. Humans can be exposed to arsenic through ingestion, inhalation, and dermal absorption. However, the most significant exposure pathway is via oral ingestion. Therefore, a comparative cross-sectional study was conducted to determine the local arsenic concentration in drinking water and hair. Then, the prevalence of arsenicosis was evaluated to assess the presence of the disease in the community. The study was conducted in two villages, namely Village AG and Village P, in Perak, Malaysia. Socio-demographic data, water consumption patterns, medical history, and signs and symptoms of arsenic poisoning were obtained using questionnaires. In addition, physical examinations by medical doctors were performed to confirm the signs reported by the respondents. A total of 395 drinking water samples and 639 hair samples were collected from both villages. The samples were analyzed using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) to determine arsenic concentration. The results showed that 41% of water samples from Village AG contained arsenic concentrations of more than 0.01 mg/L. In contrast, none of the water samples from Village P exceeded this level. Whilst, for hair samples, 85 (13.5%) of total respondents had arsenic levels above 1 μg/g. A total of 18 respondents in Village AG had at least one sign of arsenicosis and hair arsenic levels of more than 1 μg/g. Factors significantly associated with increased arsenic levels in hair were female, increasing age, living in Village AG and smoking. The prevalence of arsenicosis in the exposed village indicates chronic arsenic exposure, and immediate mitigation action needs to be taken to ensure the wellbeing of the residents in the exposed village.